Building organisations, setting minds: exploring how boards of Dutch medical specialist companies address physicians' professional performance - Maarten P. M. Debets; Milou E. W. M. Silkens; Karen C. J. Kruijthof; Kiki M. J. M. H. Lombarts (BMC, 2022)
Abstract Background Governments worldwide are reforming healthcare systems to achieve high quality and safe patient care while maintaining costs. Self-employed physicians reorganise into novel organisations to meet reconfiguration demands, impacting their work environment and practice. This study explores what strategies these novel organisations use to address physicians' professional performance and what they encounter when executing these strategies to achieve high quality and safe care. Methods This constructivist exploratory qualitative study used focus groups to answer our research question. Between October 2018 and May 2019, we performed eight focus group sessions with purposively sampled Medical Specialist Companies (MSCs), which are novel physician-led organisations in the Netherlands. In each session, board members of an MSC participated (n = 33). Results MSCs used five strategies to address physicians' professional performance: 1) actively managing and monitoring performance, 2) building a collective mindset, 3) professionalising selection and onboarding, 4) improving occupational well-being, and 5) harmonising working procedures. The MSC's unique context determined which strategies and quality and safety topics deserved the most attention. Physicians' support, trusting relationships with hospital administrators, and the MSC's organisational maturity seem critical to the quality of the strategies' execution. Conclusions The five strategies have clear links to physicians' professional performance and quality and safety. Insight into whether an MSC's strategies together reflect medical professional or organisational values seems crucial to engage physicians and collaboratively achieve high quality and safe care.